THE ESSENTIAL INTERVENTION OVER CHILDREN WITH SYNDROME OF DOWN, IN THE SEARCH FOR AN INDEPENDENCY BASED ON THE INDIVIDUAL APTITUDES (Fiep Bulletin - online, 2014)
The main target in discussing the essential intervention is to finish with the segregation that exists in the current system, because the construction the citizenship is only reached with the incorporation of diversity. An essential intervention shall not be understood only from the motor aspect, in the motor aspect, in the move acquisition, but, from its several meanings and on what it can result to. The present study intends to analyse the parents and professionals perception about the essential intervention over a child with Syndrome of Down and the search for independency, respecting and stimulating the child individual aptitude. The methodology defined for this research was the study of case inside the qualitative paradigma , once it studies the individual everyday, considering the phenomenons this individual is submitted to, through a temporal analysis. After the datas collection and analysis, the conclusion is that the success of the intervention is only possible with the existence of an interdisciplinary team because the progress onto one area applies a sequency over the development of another, once they are connected. Nevertheless, the primordial point of this interdisciplinary approach is the family, being the intermediary agent of the essential intervention, the beginning, the middle and “the end” of the process.
Keywords: Syndrome of Down; Essential Intervention; Interdisciplinary Approach